DIPLOMASI KEBUDAYAAN INDONESIA TERHADAP MALAYSIA MELALUI RUMAH BUDAYA INDONESIA - Juliani Tanjung; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research describes how the implementation of cultural diplomacy is carried out by the Indonesian government through the Indonesian Cultural House program in Malaysia and to see the level of effectiveness of the Indonesian Cultural House program by the Indonesian government in Malaysia. The purpose of the Indonesian Cultural House program in Malaysia is to develop Indonesian culture through international cultural diplomacy and encourage more international interest in visiting Indonesian cultural icons.This research uses a constructivist perspective with the level of nation state analysis and uses qualitative research methods with the main objective of collecting descriptive data that can describe the efforts of the Indonesian government in realizing the Indonesian cultural house program in Malaysia. Data collection was carried out through review of related documents, websites, and literature studies. Based on these descriptions, this research is categorized into descriptive researchThe Indonesian Cultural House program greatly benefits the international environment and Indonesian citizens living abroad. The strategy used by researchers is through: exhibitions, competitions, expert exchanges, negotiations and conferences. The impact and benefits of the collaboration between Indonesia and Malaysia in the establishment of this Cultural House. in terms of the economy, this cooperation will bring benefits to both countries in terms of increasing tourism activity from the two countries from year to year. In addition, the House of Culture has directly increased socio-cultural activities in both countries.Keywords : Indonesian Cultural House, Indonesia-Malaysia Bilateral Relations, Cultural Diplomacy, Culture of Indonesia